Replacement Peripheral Intravenous Catheters With Clinical Indication for Patient Convenience, Cost Efficiency and Reducing Nurses Workload - Narmawan Nurmawan; Ida Djafar; Hasnani Hakim; Harmiati Syafril; Syahrul Syahrul; Syahrul Ningrat (Faculty of Nursing, Universitas Hasanuddin, 2018)
Introduction: PIVCs (Peripheral Intravenous Catheters) have been widely used for clinical medical care which is having risk for phlebitis occurence. IV catheter replacement is performed when there is clinical indication such us phlebitis. The consequence of this action is patient convinence, nurse workload and patient care cost efficiency. Methode: A longitudinal study with experimental results of evidence based practice on replacement of PIVSc with clinical indication as an effort to improve patient convinience, cost efficiency and reduce nurse workload in 41 patients. Result: 41 patients attached PIVCs, 100% wanted IV catheter replacement if there was any clinical indication. 68% of patients said very uncomfortable if IV catheter routinely replaced. 16 nurse (56.25%) said there is no need to replace IV catheter regularly. 43.75% of nurses felt IV catheters rountine replacement increased the working time and 50% of the nurses felt that nurses workload was increased. Conclusions: IV catheter replacement can be performed if there is cinical indication because it can improve patient convenience, increase cost efficiency and reduce nurse workload.